2010
DOI: 10.1134/s0021364010220017
|View full text |Cite
|
Sign up to set email alerts
|

Consistent α-cluster description of the 12C(0 2 + ) “hoyle” resonance

Abstract: The near-threshold 12 C(0 2 -state structure is described as a system of three α-particles oscillating between the ground-state-like configuration and the elongated chain configuration whose probability exceeds 0.9.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…More detailed studies are required to see in which systems the features discussed here can be observed. To this end, charged quasi-particles and nuclei close to the proton drip-line [21,61,18,62,63,15,16,23,64,65,66] must be investigated. The concept of universality for neutral particles has also been explored in low and mixed spatial dimensions [67,68,69,70,71,72], and with higher angular momenta [73,74,75].…”
Section: Discussionmentioning
confidence: 99%
“…More detailed studies are required to see in which systems the features discussed here can be observed. To this end, charged quasi-particles and nuclei close to the proton drip-line [21,61,18,62,63,15,16,23,64,65,66] must be investigated. The concept of universality for neutral particles has also been explored in low and mixed spatial dimensions [67,68,69,70,71,72], and with higher angular momenta [73,74,75].…”
Section: Discussionmentioning
confidence: 99%
“…Obviously, a more detailed calculation should still be made in order to verify the extension of our results, as the two-body potential used in this toy model is not including higher partial waves, which are crucial to describe correctly the properties of 12 C [15][16][17]. A detailed analysis of the structure of the Hoyle state in 12 C, based on precise electron scattering data, can be found in [27].…”
Section: Discussionmentioning
confidence: 99%
“…We should mention here that the two-body potential used in this toy model does not consider higher partial waves, in particular d and g waves, which give a significant contribution to the properties of 12 C [15]. Much more realistic calculations can be found in [16,17].…”
Section: Formalismmentioning
confidence: 99%